The Spirit of Our Times: The Atomized, Lonely Individual. - Ucnik, Lubica (Central Europe, 2025)
This article examines Patočka's concept of Supercivilization: the idea that the atomized, lonely individual is a structural presupposition of today's societies. It argues that in historically tracing this conundrum of modern societies, Patočka points to a displacement of humans from the world that is concomitant with the birth of modern science.